Combination Approach of Border Rows and Isolation Distance for Securing Coexistence of Non‐Genetically Modified and Genetically Modified Maize. Issue 4 (1st July 2015) - Langhof, Maren; Gabriel, Doreen; Rühl, Gerhard
ABSTRACT: Border rows of non‐genetically modified (GM) maize ( Zea mays L.) planted at the GM maize field edge are thought to reduce pollen‐mediated gene flow since they act as physical barrier and dilute outgoing GM pollen. In a 3‐yr field study, we tested the efficacy of a combination of border rows and isolation distance as a coexistence measure for small‐structured agricultural landscapes. Field trials consisted of equally sized (0.8 ha) donor and recipient maize fields that were separated by either a 6‐ or 12‐m isolation distance or a combination of isolation distance with 9‐ or 18‐m border rows. Kernel color was used as a marker to quantify gene flow. The result of a general linear mixed‐effect model showed that the combination of a 9‐ or 18‐m border with isolation distance of 6 or 12 m, respectively, significantly reduced outcrossing rates in the donor‐facing field edge of the recipient fields compared with fields separated from the donor just by distance. Outcrossing rates among the variants leveled off with field depths >7.5 m. Outcrossing rates in the total recipient fields harvest decreased with increasing isolation distance from the donor field. The data from the current and previous study suggest that this reduction in outcrossing is nearly exclusively based on isolation distance. The establishment of non‐GM maize borders at the GM maize field edge to reduce the prescribed isolation distances is not recommended.